Prevalence of thyroid dysfunction in pregnancy and its association with feto-maternal outcomes: A prospective observational study from a tertiary care institute in Northern India - Roushali Kumar; Romi Bansal; Harbhajan Kaur Shergill; Priyanka Garg (Elsevier, 2023)
Background: Thyroid dysfunction in pregnancy is one of the most prominent endocrinological disorders. Physiological changes in thyroid status and non-adaptation to these changes during pregnancy lead to thyroid dysfunction resulting in feto-maternal complications. In this context, we undertook this study to estimate the prevalence of thyroid disorders in pregnant women and their association with feto-maternal outcomes. Methods: This prospective observational study was carried out in a tertiary care institute in Punjab, North India. We recruited 347 pregnant women who visited the OPD (Out Patient Department) through consecutive sampling, out of which 300 were included in our final analysis. A detailed history and clinical examination were made. Apart from routine ante-natal investigations, we estimated the TSH levels. In case of abnormal TSH values, free T4 and T3 levels were assessed. Study participants were followed till 12 weeks post-delivery to observe their obstetrical and perinatal outcomes. Results: Overall prevalence of thyroid disorders in pregnancy was 33.9%, with hypothyroidism (31.6%) being more common than hyperthyroidism (2.3%). A significant association was found between thyroid disorders and feto-maternal complications (p value < 0.001). Adverse maternal effects observed in the hypothyroid group as compared to the euthyroid group were preeclampsia (14.7% vs. 5.6%), anemia (7.4% vs. 6.1%), abortion (7.4% vs. 0.5%) and meconium-stained liquor (5.3% vs. 2.5%). Abortion (71.4%) was the main complication in the hyperthyroid group. Adverse neonatal outcomes were low and very low birth weight, low Apgar scores, respiratory distress syndrome, and meconium aspiration syndrome. Conclusion: We observed a high prevalence of thyroid disorders and their relative adverse effects. Universal screening of all women in the pre-conception period or as early as pregnancy is diagnosed, is recommended to reduce subsequent feto-maternal morbidity and mortality.